Motor profile of young taekwondo athletes - Babic, M.; Cular, D.; Kuna, D. (Sport Science - International Scientific Journal of Kinesiology, 2022)
Taekwondo is a combat sport with significant advances being made in the past two decades in organisation, competitive systems, the number of active practitioners as well as rules, and especially tactics. However, there is a significant lack of anthropometric and motor reference values. This research is trying to illuminate this particular part of great value for sports science, not examined yet. The sample for this research comprises n = 98 young taekwondo athletes out of which n = 68 are competitors and n = 30 are regular practitioners, separated within age categories into four groups: C - children (n = 24), YC - young cadets (n = 38), OC - older cadets (n = 21), and J - juniors (n = 15). They were initially tested using basic anthropometric tests (body height, body weight and BMI), followed by seven motor tests (foot taping, standing long jump, 2x15m sprint, side steps, 1-minute abdominal flexion, 1-minute squats/sit-ups, and the flamingo test) previously proven to have a correlation with success in younger taekwondo categories according to Babic, 2022. The results suggest there are linear development tendencies towards speed and strength-related latent motor abilities throughout all the observed categories. These presented reference value tables are highly utilised in practical applications, serving both as a training evaluation tool and as athlete/talent monitoring in taekwondo.